Teceres, fazeres e narrativas no ensino religioso: a cosmovisão africana como possibilidade de aplicação da Lei 10639/2003 - Vergne, Sandra Aparecida Gurgel (2016)
Weaving, doings and narratives are the methodological tools of research. Seek through bricolage, sewing, weaving, joining what is silenced, discuss over what has been produced in religious education field, in the Baixada Fluminense (State of Rio de Janeiro), as well as it’s possibility of transformation. If the libertarian proposal of Basic Ecclesial Communities in the region produced a historic moment of possibility of other perspectives, more social, collective and solidarity, the historical and social scene of the 80s, however, saw neo-Pentecostalism's growth in the region, markedly articulated with a view to encouraging economic prosperity and demonization of religions of African origin. In making the historical background regarding the racial issue in our history, we have identified a correlation of forces between racism and religion, especially in publi c school spaces. To analyze this dynamic we use the reference to authors in the field of Science of Religion, Social Sciences and Postcolonial Writings, to propose a perspective on Education which may include the African worldview as identity rescue strategy and ancestry of our black population as well as execution of the Law 10.639 / 2003, in public schools. For this I propose that, in the maintenance of Religious Education, this may be the privileged place for the rescue of the African worldview from its principles of circularity, collectivity, horizontality and integrity, transforming the field of education in an important coping territory of racism and religi ous intolerance in our country